Staged Surgery with Autologous Fibula Grafting for Humeral Non- union - A Case Report - Stephen Kamau Mwaura; Mordicai Atinga (The Annals of African Surgery)
Recalcitrant humeral non-unions after multiple fixation attempts pose a challenge to the surgeon when it comes to selecting effective and reliable management strategies. Confounding factors such as infection and bone segment loss may hamper achieving osteosynthesis even with suitable fixation. This is a case report of a 35- year-old man with a 4-year complex history of recalcitrant humerus non-union. It highlights a combination of various accessible strategies that encompass biological stimulation and mechanical stabilization toward timely bone union with minimal morbidity and return to optimal function. The use of a free fibular intramedullary strut autograft with a locking compression plate (LCP) has been infrequently described in the literature and this report adds to the data bank of this treatment strategy.